ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) DALAM MENINGKATKAN KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA BAGIAN ORGANISASI SEKRETARIAT DAERAH KOTA METRO - Mandasari, Mesie; Lukman, Iing; Wuryanti, Lestari (Universitas Malahayati, 2023)
The goal of this study is to assess the quality of the performance of Civil Servants (PNS) in the Metro City Secretariat organization. This study uses descriptive qualitative research and there are 4 metrics used, namely quantity of work, quality of work, use of time, and collaboration. There are 24 populations who are Civil Servants (PNS) in the organizational field. The concept of saturated sampling is a sampling method in which all individuals of a population are sampled. (Sugiyono, 2017). This technique is used if the population is relatively small, namely 30 people. In this study, data was analyzed in three stages: data cleaning, data presentation, and generating conclusions. Based on the findings of this survey, Metro City Regional Office employees perform well with a percentage of 41.46%.